Hubungan Dukungan Sosial Dan Perencanaan Kehamilan Dengan Kejadian Postpartum Blues Pada Ibu Remaja - Ariani Fatmawati; Nina Gartika (Jurnal BIMTAS: Jurnal Kebidanan Umtas, 2020)
Problems that arouse due to the delivery process and the addition of new family members, events after birthing, changes in life and economic status are stressfull situations that must be faced by adolescent postpartum mothers. This situation could trigger postpartum blues syndrome. The purpose of tgis study was to identify the relationship of social support and pregnancy planning with the incidence of postpartum blues in adolescent postpartum mothers. This quantitative study used cross sectional method involving 90 respondents recruits with consecutive sampling. Bivariate data analysis used chi-square. The results showed there was a relationship between social support and the incidence of postpartum blues with p value 0,000 and there was a relationship between pregnancy planning and the incidence of postpartum blues with p value 0.001. It can be concluded that Ha is accepted, so there is a relationship between social support and pregnancy planning with the incidence of postpartum blues